The Frequency of Loneliness in Elderly Women Living in Urban Areas and Affecting Factors - Ayşegül Ilgaz; Sebahat Gözüm (Dokuz Eylul University, 2020)
Background: With the increase in the rate of elderly population, the number of elderly living in urban areas has increased. Social support network of elderly decreases and loneliness increases due to changes in family structure and loss of spouses and friends in urban areas. As women live longer than men, older women experience loneliness more often Objectives: The aim of this study was to determine the frequency of loneliness and the factors affecting loneliness of elderly women living in urban areas. Methods: In this cross-sectional study, participants consisted of 296 elderly women who came to a Family Health Center. Data were collected from elderly women with descriptive characteristics form and Loneliness Scale for the Elderly. Results: It was determined that 73.3% of the elderly women were in the 65-74 age group, 19.3% lived alone and 45.9% had a relative. According to daily living activities, 97.3% of them are independent and according to instrumental daily living activities, 84.8% of them are independent. It was determined that 25% of older women "feel very lonely" and 8.8% of them "feel very lonely". Loneliness levels of elderly women living alone and without relatives were found to be high (p = .048 and p = .003). Elderly women living alone and having no relatives are 2 and 2.3 times loneliness (p = .038 and p = .002). Conclusion: Loneliness is a common problem in the elderly living in urban areas. The most important variables affecting loneliness are women live alone and have no relatives. Multidisciplinary interventions are needed to decrease loneliness of elderly women.